Photocatalytic degradation of DNOC in aqueous TiO2 dispersions - Fabbri, D. (2006)
The photocatalytic transformation of the pesticide DNOC (4,6-dinitro-o-cresol) over irradiated TiO2 suspensions was investigated in aerated aqueous solutions. Complete and relatively fast substrate degradation was achieved after irradiation with simulated solar light, being the reaction rate dependent on the initial pH. The slower evolution of the mineralization process, which can be accomplished after longer irradiation times, was evidenced.by monitoring the dissolved organic carbon decrease and the formation of nitrogen inorganic products Both the analysis of the reaction end-products and the HPLC-MS characterization of the organic intermediates are consistent with a reaction mechanism where the hydroxylation of the aromatic ring and the oxidation of the methyl group can play a major role as initial reaction steps and occurr at comparable rates. The direct reduction of nitrogroups at the semiconductor surface to form ammonium ion, inferred from the MS analysis of minor aromatic intermediates, appears to be another viable reaction path. The nearly quantitative mineralization of the pesticide has been observed after long term (3 hours) irradiation, time after which no aromatic products were detected.